Partial Purification of Bacillus cereus Enzyme Expression for Bio-Pulping of Lignin Degraders Isolated from Coptotermus curvignathus - Sharfina Mutia Syarifah; Ashuvila Mohd Aripin; Nadiah Ishak; Nosa Septiana Anindita; Mohd Firdaus Abdul-Wahab; Angzzas Sari Mohd Kassim (Engineering Proceedings)
Despite extensive research on Bacillus sp. as lignin degraders, the enzyme mechanisms involved, particularly in Bacillus cereus isolated from termite guts, remain unclear. In this study, the selected Bacillus cereus was fermented to extract the lignin-degrading enzymes to identify the enzymes responsible for lignin degradation using the sample substrate empty fruit bunch (EFB) as their sole carbon source. After 7 days of submerged fermentation (SmF), the crude enzyme was extracted, and SDS-PAGE gel was used to determine the weight of the proteins, and bands with sizes of 20 kDa–97 kDa were extracted for further analysis. The extracted proteins were partially characterized and sequenced using liquid chromatography–mass spectrometry (LC–MS/MS). The results identified 11 enzymes that are responsible for lignin degradation, such as 4-aminobutyrate aminotransferase (GABA), amidohydrolase, chemotaxis protein, serine hydrolase, GMC family protein, glycosyltransferase, phosphate binding protein PstS, ABC transporter ATP-binding protein, heme peroxidase, nitrate reductase, and nitrite reductase. The value of the mutual relationships between all the enzymes in Bacillus cereus indicates the synergistic mechanism under carbon scrutinization. Also, the peptides sequenced in this study identified various uncharacterized proteins and hypothetical proteins that might not be discovered for their protein functions. Further analysis is essential to uncover more lignin degradation enzymes that can work synergically for paper and pulp bioprocessing.